Repeated Omicron exposures redirect SARS-CoV-2-specific memory B cell evolution toward the latest variants - Kotaki, Ryutaro; Moriyama, Saya; Oishi, Shintaro; Onodera, Taishi; Adachi, Yu; Sasaki, Eita; Ishino, Kota; Morikawa, Miwa; Takei, Hiroaki; Takahashi, Hidenori; Takano, Tomohiro; Nishiyama, Ayae; et al. (Science translational medicine, 2024)
Immunological imprinting by ancestral SARS-CoV-2 strains is thought to impede the robust induction of Omicron-specific humoral responses by Omicron-based booster vaccines. Here, we analyzed the specificity and neutralization activity of memory B (B ) cells after repeated BA.5 exposure in individuals previously imprinted by ancestral strain-based mRNA vaccines. After a second BA.5 exposure, B cells with BA.5 spike protein-skewed reactivity were promptly elicited, correlating with preexisting antibody titers. Clonal lineage analysis identified BA.5-skewed B cells that had redirected their specificity from the ancestral strain to BA.5 through somatic hypermutations. Moreover, B cells with redirected BA.5 specificity exhibited accelerated development compared with de novo B cells derived from naïve repertoires. This redirected BA.5 specificity demonstrated greater resilience to viral point mutation and adaptation to recent Omicron variants HK.3 and JN.1, months after the second BA.5 exposure, suggesting that existing B cells elicited by older vaccines can redirect their specificity toward newly evolving variants.